Perspectives of teachers and students on the impact of online classrooms during the COVID-19 pandemic - Rattanawan, Prathomchai; Pakdee, Sirinthip (Frontiers in Education, 2024)
During the COVID-19 pandemic, transformation from face-to-face classrooms to online classrooms took place in higher education. This study aims to evaluate the impact of teaching and learning of this change on students' and teachers' perspectives. The study also investigated the various impact factors that hindered online teaching and learning during the COVID-19 lockdown period. Three hundred and eighty-three students and eighty-three teachers at Walailak University, Thailad who had at least three months' experience with online learning and teaching were asked to complete questionnaires that asked about their perspectives with respect to their online classroom experience. The student questionnaire asked about the quality of teachers, quality of communication, the student's work, student's concentration, and satisfaction with the online classroom experience. The teacher questionnaire asked about the teacher's perspective with respect to how the restrictions of online teaching affected teachers, students, and course. The relations between students and teachers were analyzed by chi-square test using the SPSS program version 25.0, with defined p-value as < 0.05 and < 0.10 of student and teacher perspectives respectively. Relations were found between student GPA and student work and student concentration in online classrooms. The teachers' perspective with respect to online teaching was found to be related to the restrictions that online teaching placed on teachers, students, and courses management. The results of the study show teachers' awareness about restrictions that online teaching placed on teachers, students and courses management. Institutions should prioritize and practice using educational technologies at scale, install ICT infrastructure, and engage in lifelong learning.